2019
DOI: 10.3390/sports7010026
|View full text |Cite
|
Sign up to set email alerts
|

Do Obese Children Achieve Maximal Heart Rate during Treadmill Running?

Abstract: Objective: Maximal heart rate (HR) is commonly defined as the highest HR obtained during a progressive exercise test to exhaustion. Maximal HR is considered one of the criteria to assess maximum exertion in exercise tests, and is broadly used when prescribing exercise intensity. The aim of the present study was to compare peak HR measurements during maximal treadmill running and active play in obese children and adolescents. Design: Comparison of peak heart rate during active play vs. maximal treadmill running… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…However, field tests can be performed in small groups, which create a competitive environment that can influence greater effort on the part of the participants, besides not being monotonous. Corroborating this hypothesis, Berntsen et al 41 observed that the peak HR achieved during active play was higher than that achieved in treadmill tests in obese adolescents. Another study showed that high levels of perceived competence (intrinsic motivation) are associated with higher test performance.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, field tests can be performed in small groups, which create a competitive environment that can influence greater effort on the part of the participants, besides not being monotonous. Corroborating this hypothesis, Berntsen et al 41 observed that the peak HR achieved during active play was higher than that achieved in treadmill tests in obese adolescents. Another study showed that high levels of perceived competence (intrinsic motivation) are associated with higher test performance.…”
Section: Discussionmentioning
confidence: 92%
“…39 In addition, the selection of protocols, the duration of test, and ergometers can influence the development of a predictive method by interfering in the performance and consequently in the results of exercise tests. [40][41][42] A limitation in this study was the lack of information to perform the sensitivity analyses for protocols and duration of test, but some points can be elucidated. The premise is that regardless of the protocol used, the tests must be maximal.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the lower ability of grade II obesity individuals to meet an HR>95%HR max during a treadmill test could only concern youths. According to a recent study 28 , treadmill tests would elicit ~4% lower HR peak than actives games in children with obesity. This study reinforces the idea that a high proportion of youths with obesity is not achieving a maximal effort during a treadmill test.…”
Section: Discussionmentioning
confidence: 99%